The Degree of Application of Jordanian Primary School Teachers of the RAMP Program in Teaching Arabic Vocabulary - Mohammad Ahmad Mosleh (Deanship of Scientific Research (DSR), the University of Jordan, 2020)
The study aims to reveal the degree to which teachers applied strategies for teaching Arabic vocabulary, for the second and third grades based on the RAMP program. Further, identify the most used and preferred strategies for the teacher, and the role of gender and experience in the application of vocabulary teaching strategies. Furthermore, the study sought to identify the most important repercussions of the application of vocabulary teaching strategies on students in terms of understanding and application. The sample consisted of (111) male and female teachers working in (39) schools in northern Jordan. The study followed the descriptive approach. The researcher designed a questionnaire and distributed it to participants via email. The questionnaire consisted of (17) items, covers three areas: the teacher's perception of vocabulary teaching strategies, the teacher's application of vocabulary teaching strategies, the implications of applying vocabulary teaching strategies to students. The results of the study showed that the teachers' use of the different vocabulary teaching strategies based on the RAMP program was effective and positive. The teachers slightly preferred the Vocabulary Network strategy over the other teaching strategies. Moreover, the interaction between gender and experience affected the application of the teacher to the teaching vocabulary strategies. In conclusion, teachers of the second and third grades are recommend to utilize the Ramp program in teaching new vocabulary, and to modify the curriculum and teacher manuals, in order to support the teachers and facilitate their application of the various strategies of the program.